RESISTANCE, RESILIENCE AND RISE: WOMEN’S STRUGGLE FOR FREEDOM - A STUDY OF AUTOBIOGRAPHIES OF MUSLIM WOMEN - Jainabe, S; Bharathi, T (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the struggles, resilience, and ultimate empowerment of Muslim women through the lens of their autobiographical works. Using Pardah to Piccadilly by Zarina Bhatty, My Feudal Lord by Tehmina Durrani, and A Life in Words by Ismat Chughtai as primary texts, the research delves into the challenges posed by patriarchy, socio-political structures, and cultural expectations. These narratives capture the journey from subjugation to empowerment, providing a critical analysis of the systemic barriers and personal triumphs these women encountered. The study highlights their resistance against societal norms, resilience in the face of adversities, and their role as agents of change within their communities. By employing feminist literary critique and sociological analysis, this research illuminates the broader struggles of Muslim women and their evolving roles in society.